2013
DOI: 10.1590/s0100-40422013000600020
|View full text |Cite
|
Sign up to set email alerts
|

Caracterização detalhada de material de referência certificado de carvão brasileiro

Abstract: Recebido em 31/1/12; aceito em 7/12/12; publicado na web em 12/3/13 DETAILED CHARACTERIZATION OF CERTIFIED REFERENCE MATERIAL OF BRAZILIAN COAL. The use and characterization of the first Certified Reference Material (CRM) of Brazilian coal for analytical quality control are presented. All results were determined within the limits of repeatability and reproducibility allowed under the standards. Notable among the characterization parameters was the mineral matter content (45.39%) obtained by an alternative proc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
5
0
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 12 publications
4
5
0
3
Order By: Relevance
“…Table 3 shows that Kaolinite was present in a higher percentage (62.3%), followed by quartz (31.5%) and pyrite (6.2%). Pyrite content is in accordance with [31], which e crystalline phases identified in FC sample are in accordance with the results presented by [28] and [23] which have studied Brazilian coal samples. It is important to highlight that the mass percentages obtaine by the Rietveld Method (Table 3) were calculated without the amorphous phase.…”
Section: Feed Coal Characterizationsupporting
confidence: 91%
See 2 more Smart Citations
“…Table 3 shows that Kaolinite was present in a higher percentage (62.3%), followed by quartz (31.5%) and pyrite (6.2%). Pyrite content is in accordance with [31], which e crystalline phases identified in FC sample are in accordance with the results presented by [28] and [23] which have studied Brazilian coal samples. It is important to highlight that the mass percentages obtaine by the Rietveld Method (Table 3) were calculated without the amorphous phase.…”
Section: Feed Coal Characterizationsupporting
confidence: 91%
“…Sample mass variation as a function of temperature was evaluated by ermo Gravimetric Analysis (TGA) using the TGA thermogravimetric analyzer SDTA 851 -Me ler Toledo. For the feed coal, a mass of 9.3 mg of the previously dried sample was heated using a rate of 10 ° C min -1 in an inert nitrogen atmosphere with a flow of 50 mL min -1 , and followed by an isotherm at 1200 ° C in an oxygen atmosphere during 15 min [23]. For the ashes, 7 mg of each sample was previously dried and analyzed under a dynamic nitrogen atmosphere with a flow of 50 mL min -1 and heated until reach 1200 ° C using a rate of 10 ° C min -1 .…”
Section: Ermal Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…According to the results presented, silicon oxide is a major composite of the analyzed samples, followed by aluminum, iron and potassium, which together correspond to 76% of the mass composition of ash samples. Similar values were also observed in other works, like the one carried out by Fallavena et al (2013), who analyzed coal from the south of Santa Catarina; Van Dyk et al 2009, who analyzed the coal from South Africa; and Unuma et al (1986), analyzing coal from the United States of America and in Canada. On the other hand, Song et al (2009), working with Chinese coal, observed 28% calcium oxide in ash composition; Ozbayoğlu and Özbayoğlu (2006), studying the coal from Turkey, obtained ashes containing 49.62% iron oxide, 36.85% calcium oxide and 32.95% sulfur oxide, as the maximum values after analyzing several samples.…”
Section: Characterization Of Coal Ash Samplessupporting
confidence: 87%
“…), weight %. In Brazilian coals, it is observed that sulfur is predominantly in pyrite (FeS 2 ), which has iron in its composition, which can form hematite (Fe 2 O 3 ) after oxidation 29 .…”
Section: Introductionmentioning
confidence: 99%